SARS-CoV-2 Genome Analysis of Japanese Travelers in Nile River Cruise - Sekizuka, Tsuyoshi; Kuramoto, Sanae; Nariai, Eri; Taira, Masakatsu; Hachisu, Yushi; Tokaji, Akihiko; Shinohara, Michiyo; Kishimoto, Tsuyoshi; Itokawa, Kentaro; Kobayashi, Yusuke; Kadokura, Keisuke; Kamiya, Hajime; et al. (Frontiers in Microbiology, 2020)
Japan has reported 26 cases of coronavirus disease 2019 (COVID-19) linked to cruise tours on the River Nile in Egypt between March 5 and 15, 2020. Here, we characterized the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genome of isolates from 10 travelers who returned from Egypt and from patients possibly associated with these travelers. We performed haplotype network analysis of SARS-CoV-2 isolates using genome-wide single-nucleotide variations. Our analysis identified two potential Egypt-related clusters from these imported cases, and these clusters were related to globally detected viruses in different countries.